Endomembrane‐mediated storage protein trafficking in plants: Golgi‐dependent or Golgi‐independent?. Issue 17 (10th June 2022) - Ren, Yulong; Wang, Yongfei; Zhang, Yu; Pan, Tian; Duan, Erchao; Bao, Xiuhao; Zhu, Jianping; Teng, Xuan; Zhang, Pengcheng; Gu, Chuanwei; Dong, Hui; Wang, Fan; et al.
Abstract : Seed storage proteins (SSPs) accumulated within plant seeds constitute the major protein nutrition sources for human and livestock. SSPs are synthesized on the endoplasmic reticulum and are then deposited in plant‐specific protein bodies, including endoplasmic reticulum‐derived protein bodies and protein storage vacuoles. Plant seeds have evolved a distinct endomembrane system to accomplish SSP transport. There are two distinct types of trafficking pathways contributing to SSP delivery to protein storage vacuoles: one is Golgi‐dependent and the other is Golgi‐independent. In recent years, molecular, genetic, and biochemical studies have shed light on the complex network controlling SSP trafficking, to which both evolutionarily conserved molecular machineries and plant‐unique regulators contribute. In this review, we discuss current knowledge of protein body biogenesis and endomembrane‐mediated SSP transport, focusing on endoplasmic reticulum export and post‐Golgi traffic. This knowledge supports a dominant role for the Golgi‐dependent pathways in SSP transport in Arabidopsis and rice. In addition, we describe cutting‐edge strategies for dissecting the endomembrane trafficking system in plant seeds to advance the field. Abstract : Seed storage proteins (SSPs) deposited in plant‐specific protein bodies (PBs) constitute a major protein source for humans and livestock. We discuss current knowledge on PB biogenesis and the diverse endomembrane system‐mediated intracellular SSP trafficking pathways from the cellular, molecular, and genetic perspective. We also propose feasible strategies for further dissecting SSP transport in plants.